If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = -4(2 + x) 7 + -3x = (2 * -4 + x * -4) 7 + -3x = (-8 + -4x) Solving 7 + -3x = -8 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 7 + -3x + 4x = -8 + -4x + 4x Combine like terms: -3x + 4x = 1x 7 + 1x = -8 + -4x + 4x Combine like terms: -4x + 4x = 0 7 + 1x = -8 + 0 7 + 1x = -8 Add '-7' to each side of the equation. 7 + -7 + 1x = -8 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = -8 + -7 1x = -8 + -7 Combine like terms: -8 + -7 = -15 1x = -15 Divide each side by '1'. x = -15 Simplifying x = -15
| 140+25m=400 | | 2(x-4)+3=5x | | .002x^3-.2x^2-1800=0 | | 35y-42+12y+20= | | -(k+2)=-3k-7 | | 20-9y^2=0 | | 6x=8x+30 | | 12-2(2x+10)=2 | | 36+12y=56 | | 16=6y-8 | | 3(n-5)=0 | | 8(x+6)+9=57 | | P=b+4a+cforb | | 4x-45=2x-3+x-7 | | 35x^2+10x-50= | | 9p+4=8p+8 | | 7(n+2)-3n=4+4n+10 | | 5y-9=96 | | 1x+3x= | | 6(1-3x)-2(2x-1)=18x | | 2.5n=-20 | | 9x-10y=3 | | 3s-8=9 | | 5n+3n+n+5=26 | | 5y=12x-5 | | 3x+9=56-4x | | 3a-b=1 | | a+10=27 | | 10x+1y=8 | | -5(1-5)+(-8x-2)=4x-8x | | -1/2+w=3/5 | | (x-6)+x= |